UJI KOMPOS SAMPAH RUMAH TANGGA DENGAN BERBAGAI JENIS MOL SEBAGAI BIOAKTIVATOR TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN PAKCOY (Brassica rapa L.) - Alimuddin, Suraedah; Sabahannur, St.; Rahman, Anita (AGROTEK: Jurnal Ilmiah Ilmu Pertanian, 2025)
Nationally, the highest source of waste comes from households at 46.73%. Waste can be processed into more useful materials such as compost using various MOL types as bioactivators. Compost is useful for making the soil healthy and increasing plant productivity. The purpose of this study was to test the effect of household waste compost from various types of MOL on the growth and yield of pak choi plants. This study used a Randomized Block Design (RAK) consisting of 5 treatments, namely: EM-4 Compost, Tempe MOL Compost, Rice MOL Compost, Bamboo Shoot MOL Compost, and Tempe + Rice + Bamboo Shoot MOL Compost. Each treatment was repeated 4 times so that there were 20 treatment units and each treatment unit used 5 plants. Thus, there were 60 plants in total. The parameters observed were: The results of the study showed that household waste compost with MOL bioactivator from a combination of tempeh, rice, and bamboo shoots gave the best results in the number of leaves, leaf area, fresh root weight, fresh plant weight, and consumption weight with respective values, namely 20.25 strands, 73.17 cm2, 10.02 g, 182.01 g, and 171.99 g. MOL from kitchen ingredients such as tempeh, stale rice, and bamboo shoots can be a potential alternative as a bioactivator in making household waste compost, and the resulting compost can support organic vegetable cultivation.